Rashd al-Qiblah in the Pesantren Tradition of Islamic Astronomy: The Contribution of Muhammad Faqih Maskumambang - Susiknan Azhari (Al-Hilal: Journal of Islamic Astronomy, 2026)
This article examines Muhammad Faqih Maskumambang's contribution to the transmission and practice of Rashd al-Qiblah within the pesantren tradition of Islamic astronomy in Java. Using a qualitative approach through historical-textual analysis and intellectual history, this study analyzes the socio-religious context of qibla determination in early twentieth-century pesantren communities and the role of Rashd al-Qiblah as a practical observational method. The study finds that Rashd al-Qiblah in pesantren traditions functioned not only as a technique for determining qibla orientation, but also as a medium for religious education, communal participation, and the transmission of practical astronomical knowledge. Unlike many contemporary studies that focus primarily on computational accuracy and digital verification, this article highlights the social and educational dimensions of observational astronomy in Indonesia. The study argues that Muhammad Faqih Maskumambang's contribution reflects the adaptive character of pesantren-based Islamic astronomy in mediating between scientific observation, religious authority, and everyday ritual practice in Muslim society.